2020
DOI: 10.11591/ijece.v10i1.pp1006-1016
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid algorithm to size the hospital resources in the case of a massive influx of victims

Abstract: Disaster situations either natural or made-man caused a large number of deaths and injured people. Morocco has experienced several disasters recently, the last one was the railway accident on 16 October 2018, which caused 127 serious injuries and 7 deaths. This large number was a big problem for the hospital to manage the received victims in right direction, which caused lives lost and disability. In this article, in collaboration with Mohammed (V) hospital in Casablanca city in Morocco, we suggested a solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…El Oualidi et al [28], developed a mathematical model to optimize the assignment of nurses to emergency departments in a public hospital in Morocco, and thus improve the availability of nurses in these departments. Ben Kacem et al [41] have suggested a hybrid algorithm to size needed medical resources in case of a massive influx of patients, so as to save maximum lives. In order to better manage drug provisioning in Moroccan public hospitals, Ibn El Farouk et al [42] built a decision-making tool to select relevant indicators to better measure and manage the medicines supply chain.…”
Section: Discussionmentioning
confidence: 99%
“…El Oualidi et al [28], developed a mathematical model to optimize the assignment of nurses to emergency departments in a public hospital in Morocco, and thus improve the availability of nurses in these departments. Ben Kacem et al [41] have suggested a hybrid algorithm to size needed medical resources in case of a massive influx of patients, so as to save maximum lives. In order to better manage drug provisioning in Moroccan public hospitals, Ibn El Farouk et al [42] built a decision-making tool to select relevant indicators to better measure and manage the medicines supply chain.…”
Section: Discussionmentioning
confidence: 99%
“…3 It helps to ensure better flow synchronization, especially in exceptional situations that necessitate accurate resources sizing and planning. 4,5 COVID-19 is currently submerging hospitals worldwide, with a massive influx of patients needing to be tested or hospitalized. Hospitals' capacities should be increased to meet this demand.…”
Section: Introduction the Novel Coronavirusmentioning
confidence: 99%
“…Hence, the research shifted to heuristic algorithm. Examples of heuristic algorithm are simulated annealing (SA), particle swarm optimisation (PSO) and genetic algorithm (GAs) [17][18][19][20][21]. The heuristic algorithms also have their own drawbacks [22].…”
Section: Introductionmentioning
confidence: 99%